Pengembangan Panduan Bimbingan Kelompok Dengan Teknik Modeling Berbasis Steam Untuk Meningkatkan Kematangan Karir Siswa SMP - Avilla Damaris; Nyoman Dantes; I Ketut Gading (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The background of this research is the need for guidance counselors for references to teach Group Guidance service materials in the form of guidebooks. The aims of this study were: (1) to assess that the development of group guidance manuals can increase students' career maturity; (2) describe the quality of the group guidance guide using STEAM-based modeling techniques. This study uses research and development (R&D) methods. The subject of this research is class IX students. The object contained in this study is a group guidance guidebook with STEAM-based modeling techniques. The data in this study were collected using a questionnaire technique. The results of this study indicate that: (1) guidebook research and development uses the 4D stages, namely, define, design, develop, dessimination. (2) the quality of group guidance guidebooks using STEAM-based modeling techniques that have been validated by Guidance and Counseling Experts and Middle School Guidance Teachers whose results are very high with an average score of 89 and meet the requirements for writing good guidebooks, namely (1 ) Shows high validity, (2) Shows high reliability, (3) Has practicality, (4) Able to adapt to the media used, (5) Fulfills the effectiveness of the contents of the guidebook.